Complement-dependent bystander injury to neurons in AQP4-IgG seropositive neuromyelitis optica - Duan, Tianjiao (J Neuroinflammation, 2018)
BACKGROUND: Aquaporin-4-immunoglobulin G (AQP4-IgG) seropositive neuromyelitis optica spectrum disorder (herein called NMO) is an autoimmune disease of the central nervous system in which AQP4-IgG binding to AQP4 on astrocytes results in complement-dependent astrocyte injury and secondary inflammation, demyelination, and neuron loss. We previously reported evidence for a complement bystander mechanism for early oligodendrocyte injury in NMO. Herein, we tested the hypothesis that complement bystander injury, which involves diffusion to nearby cells of activated soluble complement components from complement-injured astrocytes, is a general phenomenon that may contribute to neuronal injury in NMO. METHODS: Primary cocultures of rat astrocytes and cortical neurons were established to study complement-dependent cell death after exposure to AQP4-IgG and complement. In animal experiments, AQP4-IgG was delivered to adult rats by intracerebral injection. Cell cultures and rat brain were studied by immunofluorescence. RESULTS: In primary astrocyte-neuron cocultures, addition of AQP4-IgG and complement resulted in death of neurons nearby astrocytes. Deposition of complement membrane attack complex C5b-9 was seen on neurons nearby astrocytes, whereas C1q, the initiating protein in the complement pathway, was seen only on astrocytes. Neuron death was not seen with a complement inhibitor, with C1q- or C6-depleted complement, in pure neuron cultures exposed to AQP4-IgG and complement or in cocultures exposed to an astrocyte toxin. Intracerebral injection in rats of AQP4-IgG and a fixable dead cell fluorescent marker produced death of neurons near astrocytes, with C5b-9 deposition. Neuron death was not seen in rats receiving a complement inhibitor or in AQP4-IgG-injected AQP4 knockout rats. CONCLUSION: These results support a novel mechanism for early neuron injury in NMO and provide evidence that complement bystander injury may be a general phenomenon for brain cell injury following AQP4-IgG-targeted astrocyte death. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12974-018-1333-z) contains supplementary material, which is available to authorized users.